Matrix Effect Assessment of an Ion Chromatographic Method to Determine Inorganic Anions in Wastewater - Costa, Rachel B.; Camiloti, Priscila R.; Sabatini, Carolina A.; dos Santos, Carla E. D.; Lima Gomes, Paulo C. F. [UNESP]; Adorno, Maria Ângela T. (Springer Nature, 2018)
Inorganic anion monitoring is essential for bioreactor operation and is related for pollution control or energy and products recovery. However, there is a lack of studies validating methods for inorganic anions analyses in conditions compatible to those in bioreactor operations treating different types of wastewater. This paper provides a systematic statistical study and matrix-effect assessment for sugarcane vinasse, leachate, sewage and synthetic sewage. Sample preparation consisted of only a filtration and sample dilution. Cl−, NO2 −, NO3 −, PO4 3− and SO4 2− were determined in a Dionex ICS 5000® equipped with a chemical conductivity suppressor. Calibration curves were linear and well-adjusted between 2.5 and 50 mg L−1 for all the anions in all the tested matrices, except PO4 3− and SO4 2− in vinasse. A calibration range for PO4 3− in all tested matrices was 5.0 to 100 mg L−1, whereas a range from 5.0 mg L−1 to 50 mg L−1 was obtained for SO4 2− in vinasse. All the anions yielded recoveries in the range of 85–115% for all the tested matrices. Relative standard deviations lower than 10 and 2% were achieved for peak areas and retention times, respectively. A signal enhancement was observed for all the tested matrices and all the anions. The matrix effect level varied from −1.7 (NO2 − in vinasse) to −33.9% (Cl− in leachate). Sewage was the less affected matrix, while leachate gave higher matrix effects. Validation results and the matrix effect assessment showed that a simple sample preparation is suitable for multi-elemental analyses of inorganic anions for complex environmental samples.
Keywords: Complex matrices; Environmental chemistry; Inorganic anion determination; Standard addition method